Identification of Di/Tripeptide(s) With Osteoblasts Proliferation Stimulation Abilities of Yak Bone Collagen by in silico Screening and Molecular Docking - Chen, Yongkai; Guo, Yujie; Liu, Yusi; Zhang, Chunhui; Huang, Feng; Chen, Lingyun (Frontiers in Nutrition, 2022)
Endothelial protein C receptor (EPCR), cannabinoid receptor 2 (CBR2), and estrogen receptor α (ERα) play vital roles in osteoblasts proliferation. Also, collagen peptides have osteoblast proliferation stimulation abilities, and di/tri-peptides could be absorbed by the intestine more easily. This study obtained three di/tripeptides with potential osteoblast proliferation stimulation abilities of yak bone collagen, MGF, CF, and MF via in silico screening. Results suggested that these three peptides exhibited good absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties. They also had strong affinities with EPCR, CBR2, and ERα, and the total -CDOCKER energy (-CE) values were 150.9469 Kcal/mol, 113.1835 Kcal/mol, and 115.3714 Kcal/mol, respectively. However, further Cell Counting Kit-8 (CCK-8) assays indicated that only MGF could significantly (P < 0.05) stimulate osteoblasts proliferation at 0.3 mg/mL. At the same time, the proliferating index (PI) of the osteoblasts treated with MGF increased significantly (P < 0.05), and the alkaline phosphatase (ALP) activity decreased highly significantly (P < 0.01). In summary, MGF exhibited the potential to be an effective treatment for osteoporosis.